Effects of Smoking on Intima-Media Thickness of the Common Carotid Artery Using Ultrasonography - Asmaa Mustafa Alsiddig; Ibrahim Abdelrhim Ali (Artery Research)
Abstract Background Cigarette smoking is a causative factor in premature atherosclerosis, but the exact mechanism of smoking-induced damage to the arterial wall and its relationship to the atherosclerotic process are still largely unknown. Carotid ultrasound may help target treatment. The aim of this study was to measure carotid intima-media thickness (IMT) and carotid Doppler parameters in Sudanese smokers compared to non-smokers using ultrasound. Methods This was a retrospective, case–control, community-based study conducted between June 2021 and September 2021. The study was conducted on 100 Sudanese subjects (50 smokers as the case group and 50 non-smokers as the control group). The practical part was conducted in Khartoum State at Al Raqi University Hospital using the E-CUBE 8-ALPINION and at Yastbshroon Hospital using the Fukuda Denshi Sefius UF890AG with a high-frequency linear transducer (7–10 MHz). Scanning was performed in the supine position with the neck extended. Pulsed-wave (PW) Doppler spectral and IMT measurements were obtained. Results The mean age was 29.8 ± 4.5 years (range 24–40 years), and the mean IMT in smokers was 0.6 ± 0.06 mm, which was greater than the mean in non-smokers (0.462 ± 0.09 mm) (p = 0.000). Peak systolic velocity (PSV) was increased in smokers (40.0 ± 5.67 cm/s) compared to non-smokers (26.5 ± 5.6 cm/s) (p = 0.000), and end-diastolic velocity (EDV) was decreased in smokers (6.0 ± 1.2 cm/s) compared to non-smokers (9.8 ± 2.2 cm/s) (p = 0.000). In addition, the resistive index (RI) and the systolic-diastolic ratio (S/D) were not significantly different between smokers and non-smokers. The study showed that there was a significant positive correlation between IMT and the number of cigarettes per day in chronic smokers (p < 0.05), whereas peak systolic velocity (PSV) and end-diastolic velocity (EDV) were not affected in chronic smokers. Conclusions There was a statistically insignificant difference between the case (smokers) and control (non-smokers) groups in terms of age, body mass index (BMI), resistance index (RI), and systolic–diastolic ratio (S/D). While there were statistically significant differences in intima-media thickness (IMT), peak systolic velocity (PSV), and end-diastolic velocity (EDV), regular follow-up of individuals with a history of smoking is recommended to detect carotid intimal changes earlier.